A broadband dual‐polarized antenna with quasi‐trapezoidal patches for 5G base station application. Issue 10 (9th July 2022) - Guan, Xuehui; Zhang, Xujie; Ren, Baoping; Wang, Chuanyun
Abstract: A differential dual‐polarized patch antenna with broadband, high isolation, and low cross‐polarization level for 5G base station is presented. The antenna is composed of the radiating element, feeding structure, and reflector. The radiating element is designed with four identical smaller quasi‐trapezoidal patches to achieve a wider bandwidth, which is capacitively driven by two trapezoidal feeding patches. Impedance matching of antennas can be adjusted by tuning the size of quasi‐trapezoidal patches in the feeding portion. Finally, a prototype antenna is fabricated based on the simulated model. The measured bandwidth of the proposed antenna is about 27.8% (3.19–4.22 GHz) with VSWR<1.5, and the port isolation is better than 39.5 dB over the whole operating band. Furthermore, the proposed antenna has a stable gain of 8.55 ± 0.8 dBi and a low cross‐polarization level (<−33 dB) within the operating band.